L’integrazione delle Tecniche Cognitivo-Comportamentali e Gestaltiche nel lavoro con lo Spettro Autistico - Lorena Perrone, Elena Gigante (Phenomena Journal)
The proposal of integration between cognitive-behavioral and gestalt techniques arises from the need to design an intervention line that respects precise criteria both in theory and in practice, for the psychotherapist in the work with the subjects with autism. The work done with the disabilities requires continuous strategies to be reinvented and sewed on the patient in the "here and now". All this seems to be essential from the integrated approach, which offers continuous ideas and confirmations, not only on a theoretical but above all practical level. The integration into the technique consists precisely in the design of a work plan that allows work on several fronts, considering the totality of the subject and his needs, framing it in a specific moment of its development, in relation to the environment and the caregivers. Cognitive-behavioral techniques referring to the applied analysis of A.B.A. they integrate with the Gestalt intervention, the levels of experience together with the contact functions allow the construction of a clear and functional intervention protocol. The application of these integrated methods allows us to carefully articulate the work of the psychotherapist and other professionals in helping relationships, providing a safe container for the family and the child, for a global management.